Making high salt concentrations for optimal chromatography compatible with electrospray ionization mass spectrometry using an ion exchange membrane suppressor: Analysis of biomarkers for transporter protein inhibition as a case study - Wouters, Sam; Pijpers, Ils; Vanden Haute, Ninon; Meston, Daniel; Dillen, Lieve; Cuyckens, Filip; Eeltink, Sebastiaan (Frontiers in Analytical Science, 2022)
This study reports on the potential of using ion-exchange suppressor technology in liquid chromatography—electrospray ionization mass spectrometry workflows. The aim was to use high salt concentrations to improve separation performance, while overcoming the resulting significant ion suppression during electrospray ionization. As a case study, we apply suppressor technology to the hydrophilic interaction liquid chromatography separation and detection of taurine and glycochenodeoxycholate sulfate, endogenous biomarkers for organic anion transporter protein inhibition. The desired chromatographic selectivity was achieved applying 100 mM ion-pairing agent, while competing ions negatively affecting MS sensitivity were actively removed post-column from the solvent via a charged partially permeable membrane and replaced with protons, resulting in an up to 10-fold increase in detection sensitivity.